Influence of Gender and Parents Education Level on Mathematics Achievement of Madhyamik Passed Students in South 24 Parganas, West Bengal - Kundu, Dr. Arup (Voices of Teachers and Teacher Educators, 2022)
This study investigated the influence of the parents’ level of education on Mathematics achievement of secondary education (Madhyamik) students in South 24 Parganas district of West Bengal. The study utilized a descriptive and inferential survey research design. A sample of 430 Class XI students from 12 schools participated in the study. The sample of the study was selected through simple random sampling techniques. The mathematics score of the Madhyamik examination was used to assess the academic achievement of mathematics. The data were analysed using t-test and F-test inferential statistics on MS Excel and SPSS-23. The result showed that Mathematics achievement was not genderindependent. Male students generally achieved higher mathematics scores, than female students. Further, data showed that the parents’ education levels have significant influence on the mathematics achievement. The finding indicated that higher parents’ education were indeed amenities to the acquisition of higher scores in mathematics.